An analysis on the variability of the tilapia lake virus (TiLV) whole genome to aid in detection and treatment target - Lontok, Rain Allisha M. (Animo Repository, 2023)
Tilapia is one of the most important farmed fish worldwide for its affordability, marketability, adaptability, and hardiness in resisting disease. However, huge losses of cultured tilapia in an Israeli tilapia farm led to the discovery of the tilapia lake virus (TiLV) in 2014. It has since spread to four (4) continents and sixteen (16) countries, causing a huge threat to the global tilapia aquaculture industry for its high mortality rates reaching up to 90%. As a novel virus, much of its basic foundation is still unknown, including its genetic information and variability that has led to its rapid spread. Thus, the study aims to learn about the genetic variability of the TiLV genome to aid in detection and treatment target. An evaluation on the genomic variability was conducted through MEGA11 on twenty-two (22) TiLV genomes collected from eight (8) countries over a decade. It was found through pairwise distance estimation that segments 9 and 10 of the TiLV genome have remained largely conserved, making it a good target for virus detection. Four (4) primers each for both segments were chosen out of seventy-one (71) designed primers through NCBI Primer-BLAST with a GC% content between 50-60 and specificity for selected strains of well-supported nodes in the segments’ phylogenetic tree (lnL = -1116.19 and -1162.96, bootstrap valuesremoved). For the treatment target, the most conserved regions could not be fully evaluated due to the unknown properties of the hypothetical proteins, so the relatively conserved segment 1 coding for the putative PB1 gene was determined as the best treatment target. It was also found that the nucleotide frequency of a strain from Israel collected in 2011 (Til-4-2011) displayed a vastly different pattern compared to the rest of the sequences. The findings of this study are significant as it was able to establish certain genetic information that was previously lacking, including the genetic variation between the segments to determine the most conserved and varied regions, as well as the nucleotide compositions between the different strains. Geographical origin was also found to play a role in the reassortment of the virus as well-supported clades tended to come from the same region.